Correction to: On statistical convergence and strong Cesàro convergence by moduli - Fernando León-Saavedra; M. del Carmen Listán-García; Francisco Javier Pérez Fernández; María del Pilar Romero de la Rosa (Journal of Inequalities and Applications, 2023)
Abstract We correct a logic mistake in our paper “On statistical convergence and strong Cesàro convergence by moduli” (León-Saavedra et al. in J. Inequal. Appl. 23:298, 2019).